Alternate splicing of the p53 inhibitor HDMX offers a superior prognostic biomarker than p53 mutation in human cancer. - Lenos, K; Grawenda, A; Lodder, K; Kuijjer, M; Teunisse, A; Repapi, E; Grochola, L; Bartel, F; Hogendoorn, P; Wuerl, P; Taubert, H; Cleton-Jansen, A; et al. (2012)
Conventional high-grade osteosarcoma is the most common primary bone malignancy. Although altered expression of the p53 inhibitor HDMX (Mdmx/Mdm4) is associated with cancer risk, progression, and outcome in other tumor types, little is known about its role in osteosarcoma. High expression of the Hdmx splice variant HDMX-S relative to the full-length transcript (the HDMX-S/HDMX-FL ratio) correlates with reduced HDMX protein expression, faster progression, and poorer survival in several cancers. Here, we show that the HDMX-S/HDMX-FL ratio positively correlates with less HDMX protein expression, faster metastatic progression, and a trend to worse overall survival in osteosarcomas. We found that the HDMX-S/HDMX-FL ratio associated with common somatic genetic lesions connected with p53 inhibition, such as p53 mutation and HDM2 overexpression in osteosarcoma cell lines. Interestingly, this finding was not limited to osteosarcomas as we observed similar associations in breast cancer and a variety of other cancer cell lines, as well as in tumors from patients with soft tissue sarcoma. The HDMX-S/HDMX-FL ratio better defined patients with sarcoma with worse survival rates than p53 mutational status. We propose a novel role for alternative splicing of HDMX, whereby it serves as a mechanism by which HDMX protein levels are reduced in cancer cells that have already inhibited p53 activity. Alternative splicing of HDMX could, therefore, serve as a more effective biomarker for p53 pathway attenuation in cancers than p53 gene mutation.